Latihan Koor sebagai Media Penguatan Partisipasi Remaja Gereja: Peran Mahasiswa IAKN Tarutung dalam Pengabdian di HKBP Lumban Nabolon - Juwita Sipahutar; Wita Meilani Sihite; Yosef Aprian Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The low involvement of teenagers in church service activities is a challenge experienced by many local churches, including HKBP Lumban Nabolon. This community service activity aims to encourage the active participation of Naposo Bulung teenagers in church services through a musical arts approach, especially choir practice. IAKN Tarutung students who are implementing the Practical Lecture and Community Service (KPPM) program take on the role of facilitators, vocal trainers, and motivators in fostering teenagers to be more actively involved in church liturgy. The method used in this activity is a participatory approach through observation, interviews, direct training, and group reflection. The findings show that choir practice not only improves the technical vocal skills of teenagers, but also builds self-confidence, togetherness, and commitment to service. As many as 70% of teenagers who were previously passive began to show enthusiasm in participating in practice and performing in worship. This activity also has an impact on improving relations between Naposo Bulung members and the formation of a more lively service climate among the younger generation. These results show that church music, when carried out in a focused and inclusive manner, can be an effective means of empowering teenagers. This community service activity recommends that choir practice be made a routine church development program with ongoing mentoring from the church and educational institution partners.